Gambaran C-Reactive Protein Pada Pasien Tuberkulosis Paru di Puskesmas Naibonat Kabupaten Kupang - Ni Ketut Yuliana Sari; Adrianus Ola Wuan; Aldiana Astuti; Novian Agni Yudhaswara; Agnes Rantesalu; Ikhsan Rasidin (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Tuberculosis is a chronic infectious disease induced by the bacterium Mycobacterium tuberculosis and can attack human organs, especially the lungs. The entry of this antigen causes the release of various pro-inflammatory cytokines which cause liver cells to synthesize acute phase proteins such as C-Reactive Protein (CRP). C-Reactive Protein is a type of alpha globulin protein that appears in the blood in response to inflammation in the body. The aim of this study was to determine the description of CRP in pulmonary tuberculosis patients at the Naibonat Community Health Center. The method used is descriptive with a cross sectional study design method. This research was carried out at the Naibonat Health Center Laboratory, Kupang Regency from February to April 2024. The examination method used was the qualitative latex agglutination method. The results of CRP examination on pulmonary TB patients from a total of 23 respondents obtained reactive results for 8 samples (35%) and non-reactive results for 15 samples (65%). Based on the results of reactive CRP, the highest number was found in males, 6 people (26%), while the highest number was found in the age range 12-25 years, 4 patients (Teenagers) (17%), with the highest length of treatment at 0 -2 months (intensive stage) as many as 6 patients (35%), with the highest patient status being new TB as many as 8 patients (35%), with the highest treatment status being non-resistant as many as 6 patients (26%).